Southeast Kansas Crop Production Summary – 2018 - G. F. Sassenrath; L. Mengarelli; J. Lingenfelser; X. Lin (Kansas Agricultural Experiment Station Research Reports, 2019)
This is a summary of the crop production conditions in southeast Kansas in 2018, and the results of the variety testing for corn, soybean, sorghum, sunflower, and wheat.
Keywords: crop production; corn; wheat; soybeans; sorghum; sunflowers